2005
DOI: 10.1371/journal.pmed.0020180
|View full text |Cite
|
Sign up to set email alerts
|

Uncomplicated Monochorionic Diamniotic Twins and the Timing of Delivery

Abstract: Cleary-Goldman and d'Alton discuss the implications of a new study in PLoS Medicine examining the risk of fetal death in uncomplicated monochorionic diamnotic twin pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 8 publications
(12 reference statements)
1
20
0
4
Order By: Relevance
“…12 One possible concession is to offer delivery of these apparently uncomplicated monochorionic twins at approximately 34 to 35 weeks of gestation after antenatal corticosteroid administration and appropriate counseling regarding the pros and cons of expectant management versus elective preterm delivery. 6 Based on our results and on recent observations regarding the excess risk of respiratory complications after near term twin delivery, 13,14 we believe that our policy of offering elective preterm birth after 36 completed weeks of gestation is a more reasonable compromise.…”
Section: Commentmentioning
confidence: 68%
See 2 more Smart Citations
“…12 One possible concession is to offer delivery of these apparently uncomplicated monochorionic twins at approximately 34 to 35 weeks of gestation after antenatal corticosteroid administration and appropriate counseling regarding the pros and cons of expectant management versus elective preterm delivery. 6 Based on our results and on recent observations regarding the excess risk of respiratory complications after near term twin delivery, 13,14 we believe that our policy of offering elective preterm birth after 36 completed weeks of gestation is a more reasonable compromise.…”
Section: Commentmentioning
confidence: 68%
“…Whereas the results of the study of Barigye et al 5 seem to suggest that 32 weeks of gestation may be a reasonable date for elective preterm delivery to avoid unexpected IUFDs, the inherent risks of prematurity at that gestational age remain significant. 6 In the absence of randomized studies, balancing the risk of elective preterm birth versus the risk of single or double IUFD is still challenging. 6 As a result, we carried out this retrospective cohort study to reassess the prospective risk of IUFD in our monochorionic twin population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, even this subset of apparently " uncomplicated " MC twins was found to be at a considerable excess risk (about 4 % per pregnancy) of IUFD [2] . In their discussion of the unexpected IUFD rate among these MC twins, Cleary-Goldman and D ' Alton [5] suggested that elective preterm delivery (at 34 -35 weeks) might be a reasonable policy to avoid unexpected IUFD. Several other hospital-based studies found a much lower risk, but had an important disadvantage of coming from tertiary centers, some with special interest in MC twinning, which do not represent the population at large.…”
Section: Prophylaxismentioning
confidence: 99%
“…The incidence of perinatal complications is reportedly higher in pregnant women with monochorionic twins [3][4][5][6][7]. Chorionicity can be reliably determined in the first trimester of pregnancy by using non-invasive ultrasonography [8].…”
Section: Introductionmentioning
confidence: 99%